2014
DOI: 10.1007/s00467-014-2892-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum suPAR levels help differentiate steroid resistance from steroid-sensitive nephrotic syndrome in children

Abstract: From ROC curve analysis, we demonstrated the significance of the suPAR level in predicting SRNS with a high specificity but low sensitivity. However, the clinical value of suPAR to predict steroid resistance and guide therapy remains to be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
0
18
1
2
Order By: Relevance
“…Thus, 364 studies were initially included, among which 306 studies were excluded after reading the title and abstract. After reading the full text, another 29 studies were excluded; therefore, 29 studies were finally included 9–11 21–46. A flow chart of the study selection process is presented in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 364 studies were initially included, among which 306 studies were excluded after reading the title and abstract. After reading the full text, another 29 studies were excluded; therefore, 29 studies were finally included 9–11 21–46. A flow chart of the study selection process is presented in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In total, there were 18 studies9 10 22–27 30 33–35 37 38 40–42 46 in which the concentrations of suPAR were compared between primary FSGS and the normal control group. The overall results showed that the level of suPAR in the primary FSGS group was significantly higher when compared with that in the normal control group (p<0.001; SMD: 2.56; 95% CI 1.85 to 3.28; I 2 =96.9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contradictory results had been declared. In 2015, Peng Z et al, showed that serum suPAR may help to differentiate steroid resistance from steroid-sensitive NS in children with high specificity but low sensitivity [21].…”
Section: Resultsmentioning
confidence: 99%
“…It may be possible that suPAR plays a role in both genetic and non-genetic forms of rFSGS ( 9 ); even so rFSGS is generally less prominent in genetic forms of FSGS ( 8 ). Some reports show inconsistencies in associations of suPAR and rFSGS in patients with advanced CKD and reduced eGFR in pediatric ( 22 , 23 ) and adult FSGS patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%